Biomedical research of chopped meat products with complex additive«Maltovin» - Літвінова, Інна Олександрівна; Савінок, Оксана Миколаївна; Шафран, Леонід Мойсейович; Третьякова, Олена Володимирівна (Eastern-European Journal of Enterprise Technologies, 2014)
The results of biomedical research on the impact of additive «Maltovin » with antioxidant properties on the state of the antioxidant system of animals by biochemical parameters are given in the paper. The main objective of the research was to determine the toxicological safety of using chopped meat products with complex additive «Maltovin» for biological objects and solve the problem of improving the quality of meat products by increasing their resistance to oxidation processes. Subchronic administration of the additive “Maltovin” in chopped meat products, which have passed the preliminary heat treatment, to the diet of laboratory rats did not result in any statistically significant changes in indicators of morphometry, metabolism and overall functional state of experimental animals compared with the control group. There was no lag in the weight gain, structure indicators and ratio of blood cells, hemoglobin content in experimental animals, behind that of control animals. The activity of key enzymes of carbohydrate and protein metabolism changed insignificantly that proves the lack of the negative impact of additive and foods with it on the hepatorenal system. Safety of using the additive is also confirmed by indicators, characterizing preserving the balance between pro- and antioxidant systems (by indicators of MDA, DP, GR, G-6, FDG) of animals. Analysis of the obtained results showed that “Maltovin” can be used as an effective antioxidant additive, which promotes preserving the quality of meat products with significant fat content and does not affect the state of the main physiological systems.